Economic Reforms and the Poor : Social Action Programs and Social Funds in Sub-Saharan Africa - Marc, Alexandre; Graham, Carol; Schacter, Mark (World Bank, Washington, DC, 2012)
For many African countries, and for developing countries in other regions, the latter half of the 1980s was a turning point in the struggle to alleviate poverty. In response to a marked deterioration in the living standards of the poor, caused by an economic crisis and the austerity measures instituted to control it, governments added explicit poverty alleviation objectives to their development policies. In cooperation with external agencies, they began to design and implement interventions such as social action programs (SAPs) and social funds (SFs) to protect the poor and some vulnerable groups from the harmful effects of the economic situation and from the transitory negative effects of economic reform. There has been a growing acceptance of these interventions in Africa as the World Bank has placed greater emphasis on protecting the poor during adjustment. The present study previewed in this brief, reviews the experience of twelve SAPs and SFs in sub-Saharan Africa. Because a number of the programs are still in progress at this writing, it is too soon to analyze their effects on poverty reduction in depth. However, performance information is increasingly available on the implementation of these programs. This report is based on data gathered from project documents and task managers of the projects and on findings by the authors during field visits.